Sound advice : becoming a better children's choir conductor - Bartle, Jean Ashworth (Oxford scholarship online, 2023)
The vast array of skills needed by today's conductor of children's choirs is covered in this text. Everything from the development of musicianship through singing & literacy in the choral setting, to the challenges of conducting an orchestra, working with parents & working with staff, is outlined.
Keywords: Choral conducting; Children's choirs; Choral singing : Instruction and study : Juvenile; Music